A delayed diagnosis of Mounier-Kuhn syndrome. (2nd June 2014) - Gouder, Caroline; Bilocca, David; Fsadni, Peter; Montefort, Stephen
Abstract : Following a provisional diagnosis of asthma of several years' duration by his general practitioner, a 43-year-old otherwise healthy man who was a non-smoker was referred to a pulmonologist with worsening productive cough and exertional breathlessness. A thoracic CT scan revealed dilated airways (tracheal diameter 35 mm, left bronchial diameter 20 mm, right bronchial diameter 18 mm). Inflamed and easily collapsible airways were seen on bronchoscopy. The patient remained stable and was followed up with regular spirometry. A follow-up CT scan 7 years later showed tracheobronchomegaly (tracheal diameter 42 mm, left bronchial diameter 25 mm, right bronchial diameter 23 mm) with large cystic spaces consistent with Mounier-Kuhn syndrome. Repeat bronchoscopy showed a massively dilated trachea and generalised collapse on expiration with a dilated thin-walled bronchial tree. He was deemed ineligible for lung transplantation due to the extent of airway involvement making it difficult to anastomose donor lung to native tissue.